The Influence of Nanoparticle Properties on Oral Bioavailability of Drugs - Wang, Yuanyuan (Int J Nanomedicine, 2020)
Oral administration has been the most common therapeutic regimen in various diseases because of its high safety, convenience, lower costs, and high compliance of patients. However, susceptible in hostile gastrointestinal (GI) environment, many drugs show poor permeability across GI tract mucus and intestinal epithelium with poor oral absorption and limited therapeutic efficacy. In recent years, nanoparticulate drug delivery systems (NDDS) have become a hot research spot because of their unique advantages including protecting drug from premature degrading and interacting with the physiological environment, increasing intracellular penetration, and enhancing drug absorption. However, a slight change in physicochemistry of nanoparticles can significantly impact their interaction with biological pathways and alter the oral bioavailability of drugs. Hence, this review focuses on the factors affecting oral bioavailability from two aspects. On the one hand, the factors are the biochemical and physiological barriers in oral drugs delivery. On the other hand, the factors are the nanoparticle properties including size, surface properties, and shape of nanoparticles.